AB1168 Touch study: technology and outcomes used in clinic in a day hospital. (15th June 2017) - Cunha-Miranda, L; Miguel, C; Silva, C; Barcelos, F; Marques, R; Trinca, R; Cardoso, A; Borges, J; Fernandes, S; Santos, H; Faustino, A
Abstract : Background: Patient reported outcomes PRO are a key element in the global evaluation of patients, especially those followed in a day hospital. The use of touchscreen computers is one of the new features in the day hospital of Instituto Português de Reumatologia. Objectives: to evaluate the transition from paper to touchscreen computers technology of the PRO in use in Reuma.pt Methods: We considered a step up model of comparison with 2 months intervals one before the use of the touchscreen computers, one two months after the introduction of touchscreen computers and a third after an intermediate evaluation (comparison between interval 0 and 1) of the results.A specific formation to physicians and nurses to be aware of missing data from non-total completion of the questionnaires was introduced between the first and second evaluation. The percentage of questionnaires totally completed by number of patients were obtained for every period and diagnosis Results: 631 day hospital appointments were evaluated according to diagnosis and interval and the percentage was obtained (Table 1 ) Only HADS had a significative (p<0.000) improvement for every disease, with the use of the touchscreen computers from interval 1 to 2. On our intermediate evaluation comparing paper to tablet we saw a lower percentage of questionnaires fully completed (although not statistical significative) and a formal awareness formation addressing the causes was made with all the physicians and nurses of the day hospital. The PRO from Reuma.pt was not developed for tablets and some issues regarding missing data associated with that was found Conclusions: The use of technology can contribute for better data in Reuma.pt and other national registries by saving time (medical and nurse) for clinical evaluation, by integrating patients in their evaluations and by cost reduction, and carbon footprint. Issues regarding the adaptability of software to tablet technology have to be addressed to insure an overall improvement. Disclosure of Interest: None declared